2017
DOI: 10.1097/mib.0000000000001047
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation with 2000 IU of Cholecalciferol Is Associated with Improvement of Trabecular Bone Mineral Density and Muscle Power in Pediatric Patients with IBD

Abstract: We observed an improvement in bone and muscle parameters after cholecalciferol substitution in pediatric patients with IBD. Therefore, vitamin D substitution can be considered in such patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 48 publications
0
31
0
1
Order By: Relevance
“…In IBD pediatric patients, 2000 IU/day of vitamin D 3 for 6 months was more effective in raising serum 25(OH)D concentrations > 30 ng/ml than 400 UI/day or doses up to 2000 IU of vitamin D 2 [ 407 , 408 ]. On the other hand, supplementation with 2000 IU/day of vitamin D 3 for 13.8 months improved trabecular BMD, cortical bone cross-sectional area, and maximal muscle power in 55 IBD patients [ 409 ].…”
Section: Extraskeletal Actions Of Vitamin Dmentioning
confidence: 99%
“…In IBD pediatric patients, 2000 IU/day of vitamin D 3 for 6 months was more effective in raising serum 25(OH)D concentrations > 30 ng/ml than 400 UI/day or doses up to 2000 IU of vitamin D 2 [ 407 , 408 ]. On the other hand, supplementation with 2000 IU/day of vitamin D 3 for 13.8 months improved trabecular BMD, cortical bone cross-sectional area, and maximal muscle power in 55 IBD patients [ 409 ].…”
Section: Extraskeletal Actions Of Vitamin Dmentioning
confidence: 99%
“…60 In pediatric IBD patitents conflicting data have been reported. 61, 62 More systematic studies in pediatric and adult IBD patients need to be conducted to identify factors determining the clinical response to vitamin D and Ca 2+ supplementation, the form and route of administered vitamin D, with careful monitoring of the parameters of bone mass, bone turnover, and mineral homeostasis. The need for such systematic approach is further justified by identification of at least a subset of IBD patients with inappropriate hypercalcitriolemia (elevated serum 1,25(OH) 2 D 3 ).…”
Section: Vitamin D3 and Calciummentioning
confidence: 99%
“…The cohort study of Hradsky et al[27] was designed to assess the effect of vitamin D 3 therapy on bone health parameters and dynamic muscle function. In total, 55 patients aged 5-19 years with a diagnosis of IBD were included.…”
Section: Resultsmentioning
confidence: 99%
“…Another study showed a similar response after weekly dosing of 50,000 IU D 3 for 6 wk[23]. In a third study, 2000 IU D 3 daily was able to achieve a mean s-25OHD above 30 ng/mL in the study population throughout the course of treatment[27]. Both 5000 IU/10 kg vitamin D 3 per week and 10000 IU/10 kg vitamin D 3 per week for a period of 6 wk were able to raise s-25OHD above 30 ng/mL at week 8 in one of the trials; however, this effect was lost by week 12[24].…”
Section: Discussionmentioning
confidence: 98%